Single color attribute index for shade conformity judgment of dental resin composites - Yong-Keun Lee (Wolters Kluwer Medknow Publications, 2015)
Introduction: Commercial dental resin composites under the same shade designations show color discrepancies by brand. Moreover, three Commission Internationale de l'Eclairage (CIE) color coordinates show significant variations by measurement method; therefore, direct comparisons of the color coordinates based on different methods are meaningless. This study aimed to assess a hypothesis that a new color attribute index (CAI), which could reduce the color coordinate variations by measurement method, was applicable for the shade conformity judgment of dental resin composites. The Hypothesis: CAI is applicable in the shade conformity judgment of commercial dental resin composites. Using the CIE color coordinates of shade guide tabs and resin composites, combined color indices such as Wa = CIE aFNx01 × DEFNx01 ab /C ab FNx01 and Wb = CIE bFNx01 × DEFNx01 ab /C ab FNx01 were defined, in which DEFNx01 ab was the color difference with a standard white tile. Ratio of Wa/Wb to that of an arbitrary reference shade (A2) in the same brand and measurement was defined as the CAI. The CAI values were significantly different by the shade designation and showed a logical trend by the shade designation number. The CAI of commercial resin composites and the keyed shade guide tabs showed overlaps. Evaluation of the Hypothesis: The CAI might be used to judge the shade conformity of resin composites using the values based on different measurement methods. The application of the CAI, instead of conventional three-color coordinates, could efficiently simplify the shade conformity judgment of commercial resin composites. Although the hypothesis of the present study was partially confirmed, further studies for the practical application of this index are highly recommended.